234k views
0 votes
Simplify the radical expression attached below.

Simplify the radical expression attached below.-example-1
User Alex Riina
by
5.5k points

2 Answers

4 votes
It’s gonna be radical 10x/ 4x.
User Vikas Gupta
by
5.2k points
3 votes
Answer:
(√(10x))/(4x)

===========================================================

Work Shown:

The idea is to multiply top and bottom by sqrt(8x) to make the denominator rational (ie get rid of the square root)


(√(5))/(√(8x)) = (√(5)*√(8x))/(√(8x)*√(8x))


(√(5))/(√(8x)) = (√(5*8x))/(√(8x*8x))


(√(5))/(√(8x)) = (√(40x))/(√((8x)^2))


(√(5))/(√(8x)) = (√(4*10x))/(8x)


(√(5))/(√(8x)) = (√(4)*√(10x))/(8x)


(√(5))/(√(8x)) = (2*√(10x))/(8x)


(√(5))/(√(8x)) = (√(10x))/(4x)

where x > 0 for each step shown above

note: refresh the page if the math symbols do not show up

User Kmfk
by
5.3k points